Kajian Hukum Islam terhadap Tradisi Talitihan: Analisis Praktik Lokal di Desa Batangsari, Kecamatan Sukasari, Kabupaten Subang - Itang Komar; Jidan Zenidan (Program Studi Hukum Keluarga Islam, 2024)
Talitihan is a term in Sundanese which means giving something in the form of groceries such as rice, sugar,instant n oodles, cakes and money, gifts and others to people who are going to get married. The aim is to helpfellow Muslims and connect friendship ties to strengthen ukhuwwah Islamiyyah. The purpose of this study wasto find out the practice of Talitian carried ou t by all the people of the Batangsari Village, Subang Regencyand a review of Islamiclaw on the practice of Talitihan in the implementation of marriages in the BatangsariVillage, Subang Regency. The type of research that researchers use in this study is a phenomenologicalapproach. This study isdescriptive in nature, providing a complete and detailed description of the problems ofIslamic law against the Talitihan tradition during the marriage ceremony in the Batangsari Village, SubangRegency. Thisresearc h method is qualitative. Data collection techniques are carried out in 3 ways, namelyobservation, interviews and documentation. The results of this studyindicate that a tradition that hasdeveloped in the people of the Batangsari Village, Subang Regency i s that they demand the Talitihan(donation) they have given back by reprimanding or reminding the person who has received the Talitihan, ifthe return is not in accordance with the gift, either in the form of goods nor money. The uniqueness of theTalitiha n tradition in the Batangsari Villageis that in this case Talitian's gifts or donations must be returnedin accordance with the gift. Review of Islamic Law in the tradition that developed in the Batangsari Village,Subang Regency, namely asking for Talitih an(donations) that have been given back is permissible, becausethe form of grants applied in the Batangsari Hamlet community expects a return in the grant, if the person hegives does not reciprocate grant, then he has the right to ask for it back.